Biocompatibility of novel chitosan paste derivatives in cultured primary human skin fibroblasts in vitro - Abdull Rasad, Mohammad Syaiful Bahari; Shamsuddin, Shaharum; Halim, Ahmad Sukari; Yusof, Norimah (Penerbit Universiti Sains Malaysia, 2007)
Biocompatibility of novel chitosan paste derivatives in cultured primary human skin fibroblasts in vitro.